Export Market Risk and the Role of State Credit Guarantees - Inga Heiland; Erdal Yalcin (Center for Economic Studies and ifo Institute (CESifo), 2015)
Many countries offer state credit guarantee programs to improve access to finance for exporting firms. In the case of Germany, accumulated returns to the scheme deriving from risk-compensating premia have outweighed accumulated losses over the past 60 years. Why do private financial agents not step in? We build a simple model with heterogeneous firms that rationalizes demand for state guarantees with specific cost advantages of the government. We test the model's predictions with detailed firm-level data and find supportive evidence: State credit guarantees in Germany increase firms' exports. This effect is stronger for firms that are dependent on external finance, if the value at risk is large, and at times when refinancing conditions are tight.
Keywords: F36; G28; H25; H81; 330; state export credit guarantees; credit constraints